Program Pelatihan Masa Persiapan Pensiun pada Karyawan PT. Krakatau Steel - Ratu Indah Purnama Sari; Ahmad Fauzi; Nandang Faturohman (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
Retirement is something that cannot be avoided by workers, in retirement usually many employees who do not have the readiness to face changes in lifestyle such as identification of problems that researchers can at PT. Krakatau Steel namely lack of psychological readiness for employees who will face retirement, lack of self-understanding makes employees of PT. Krakatau Steel has difficulty making a productive life after retirement, many retirees who have no productive attitude after not working, and lack of financial readiness after retirement. The purpose of this study was to determine the Retirement Preparation Period (MPP) training for employees of PT. Krakatau Steel, to find out how to foster productive attitudes in PT. Krakatau Steel, and to find out the Retirement Preparation (MPP) training program in fostering productive attitudes towards employees of PT. Krakatau Steel. The method used in this study is a qualitative method by conducting interviews, observation and documentation to one person in charge of training and nine trainees. The results of this study in the Retirement Preparation Period (MPP) training for employees of PT. Krakatau Steel has